Matematyka

Autorzy:A. Drążek, E.Duvnjak, Ewa Kokiernak-Jurkiewicz

Wydawnictwo:WSiP

Rok wydania:2016

Od wyrażenia 3x²+y²-2xy odejmij podwojone wyrażenie -xy-2y²+2x² 4.2 gwiazdek na podstawie 5 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

Od wyrażenia 3x²+y²-2xy odejmij podwojone wyrażenie -xy-2y²+2x²

5
 Zadanie

6
 Zadanie

7
 Zadanie
8
 Zadanie
9
 Zadanie
10
 Zadanie
11
 Zadanie
12
 Zadanie
13
 Zadanie

`P=3x^2+y^2-2xy`

`D=-xy-2y^2+2x^2`

`P-2D=3x^2+y^2-2xy+2xy+4y^2-4x^2=5y^2-x^2`

`5y^2-x^2=5*sqrt(5)^2-(-2)^2=25-4=21`